Adhesive composition, adhesive, adhesive sheet, and optical film with adhesive layer
By using a special (methyl) acrylic polymer (A) adhesive combination, the molecular weight distribution and internal agglomeration force are adjusted to solve the problem of lack of tightness and stretching toughness of acrylic membrane and adhesive layer, and realize The high smoothness and excellent durability of the adhesive layer.
Patent Information
- Application Number
- CN202110184299.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-13
- Filing Date
- 2021-02-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-02-10
AI Technical Summary
In the prior art, it is difficult to ensure adhesion with a well-known adhesive layer, and there is a shortage in tensile toughness, which may cause problems of floating or peeling under durable conditions.
A sticky combination, which contains (methyl) acrylic polymer (A), and adjusts its molecular quantity distribution through gel penetration. The peak molecular weight is between 800,000 and 1.2 million, and the concentration is 20 % by mass. It is dissolved in a mixed solvent in acetate and acetone to achieve excellent viscosity and internal agglomeration.
The high smoothness and excellent durability of the adhesive layer are realized, and the interface with the adhesion is avoided with floating or peeling, and the overall performance of the optical membrane is enhanced.
Smart Images

Figure CN113249062B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition, an adhesive, an adhesive sheet, and an optical film with an adhesive layer, and in particular to an adhesive composition, an adhesive, an adhesive sheet, and an optical film with an adhesive layer that are useful in optical films such as polarizing plates. Background Art
[0002] In recent years, touch screens that combine display devices and input means have been widely used as display panels for various electronic devices. Touch screens are mainly divided into resistive film type, electrostatic capacitive type, optical type and ultrasonic type. Resistive film type includes analog resistive film type and matrix resistive film type, and electrostatic capacitive type includes surface type and projection type.
[0003] In the touch screens of mobile electronic devices such as mobile phones or tablet terminals that have recently attracted attention, projection-type electrostatic capacitive touch screens are mostly used. As a projection-type electrostatic capacitive touch screen in such mobile electronic devices, for example, a touch screen is proposed in which a liquid crystal display device (LCD), an adhesive layer, a transparent conductive film (indium tin oxide: ITO), a glass substrate, a transparent conductive film (ITO) and a protective plate such as tempered glass are stacked in order from the bottom.
[0004] As an optical component constituting the above-mentioned liquid crystal display device, a liquid crystal element is generally used. The liquid crystal element is generally obtained by placing the orientation layer of two transparent electrode substrates with an orientation layer as the inner side, configuring them in a manner of forming a predetermined interval using a spacer, sealing the periphery thereof, and clamping the liquid crystal material between the two transparent electrode substrates. Usually, a polarizer or a composite polarizer having a phase difference plate is bonded to the outer sides of the two transparent electrode substrates in the liquid crystal element via an adhesive.
[0005] As an adhesive for optical films, there is known an adhesive disclosed in Patent Document 1, for example. The adhesive contains an acrylic copolymer (A) and a curing agent (B), wherein the acrylic copolymer (A) contains structural units derived from specified monomers (a-1) to (a-4) and does not contain structural units derived from acidic group-containing monomers, and has a dispersion (Mw / Mn) of 1.5 to 2.5, which is a ratio of a weight average molecular weight (Mw) to a number average molecular weight (Mn).
[0006] The polarizing plate as an adherend of the pressure-sensitive adhesive has a structure in which a polyvinyl alcohol film (PVC layer) as a polarizer is sandwiched between two triacetyl cellulose films (TAC layers).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-193608 Summary of the invention
[0010] Technical Problems to be Solved by the Invention
[0011] In addition, with the recent demand for lighter and thinner mobile electronic devices, optical films such as polarizers are also required to be thinner. However, if the conventional triacetyl cellulose film is thinner, problems such as loss of water barrier properties will occur. Therefore, the use of acrylic films formed of acrylic resins instead of triacetyl cellulose films is being studied.
[0012] However, it is known that the acrylic film as described above is difficult to ensure adhesion with the conventionally known adhesive layer and tends to be slightly inferior in toughness to stretching. Therefore, it is known that when the acrylic film is used for a polarizer, it tends to float or peel off at the interface with the adhesive layer under durable conditions.
[0013] When the adhesive of Patent Document 1 is applied to a polarizing plate using the acrylic film described above, the adhesive has low durability because its molecular weight distribution is too narrow and its cohesive force is too high.
[0014] On the other hand, the above-mentioned adhesive is usually made into an adhesive layer in advance and used as an adhesive sheet. When the polarizing plate etc. which has been thin-filmed are used as adherends, from the viewpoint of optics etc., it is required that the surface state of the adhesive layer is in a highly smooth state. The smoothness of the adhesive layer is greatly affected by the quality of the processability when the adhesive composition is applied.
[0015] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide an adhesive composition, an adhesive, an adhesive sheet, and an optical film with an adhesive layer which are excellent in durability and good in processability when the adhesive composition is applied.
[0016] Technical means to solve technical problems
[0017] In order to achieve the above-mentioned object, first, the present invention provides an adhesive composition comprising a (meth)acrylate polymer (A), wherein, in the molecular weight distribution of the (meth)acrylate polymer (A) measured by gel permeation chromatography, the amount of components having a molecular weight of 3,000,000 or more is 15% by mass or less, and the peak molecular weight (Mp) is 800,000 or more and 1,200,000 or less, and the viscosity when the (meth)acrylate polymer (A) is dissolved in a mixed solvent of ethyl acetate and acetone containing 85% by mass of ethyl acetate so as to have a concentration of 20% by mass is 5,000 mPa·s or more and 10,000 mPa·s or less (Invention 1).
[0018] In the above invention (Invention 1), by making the adhesive composition satisfy the above properties, even if the adhesive sheet having the adhesive layer obtained from the adhesive composition is applied to an optical film such as a polarizing plate having an acrylic film (acrylic resin layer), the durability is still excellent. In addition, the adhesive composition satisfying the above properties has good processability when the adhesive composition is applied, and the surface state of the obtained adhesive layer is a highly smooth state.
[0019] In the above invention (Invention 1), it is preferred that the (meth)acrylate polymer (A) is polymerized without using a solvent having a boiling point of 70° C. or less (Invention 2).
[0020] In the above inventions (Inventions 1 and 2), it is preferred that the weight average molecular weight (Mw) of the (meth)acrylate polymer (A) is 800,000 or more and 2,000,000 or less (Invention 3).
[0021] In the above inventions (Inventions 1 to 3), it is preferred that a crosslinking agent (B) is contained (Invention 4).
[0022] Second, the present invention provides an adhesive obtained by cross-linking the adhesive composition (Inventions 1 to 4) (Invention 5).
[0023] Thirdly, the present invention provides an adhesive sheet comprising an adhesive layer (Invention 6) formed of the above-mentioned adhesive (Invention 5).
[0024] Fourthly, the present invention provides an optical film with an adhesive layer, comprising: an optical film having at least one acrylic resin layer; and an adhesive layer formed of the adhesive (Invention 5) laminated on at least one surface of the optical film (Invention 7).
[0025] In the above invention (Invention 7), it is preferred that the optical film is a polarizing plate having the acrylic resin layer as a polarizer protective layer (Invention 8).
[0026] Effects of the Invention
[0027] The adhesive, adhesive sheet, and optical film with an adhesive layer of the present invention are excellent in durability and good in processability when the adhesive composition is applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a cross-sectional view of an optical film with an adhesive layer according to one embodiment of the present invention.
[0029] Description of Reference Numerals
[0030] 10: optical film with adhesive layer; 1: adhesive layer; 2: polarizing plate; 21: polarizer; 22: first protective layer; 23: second protective layer. DETAILED DESCRIPTION
[0031] Hereinafter, embodiments of the present invention will be described.
[0032] [Adhesive composition]
[0033] The adhesive composition of one embodiment of the present invention (hereinafter sometimes referred to as "adhesive composition P") contains a (meth)acrylate polymer (A), and preferably further contains a crosslinking agent (B). In addition, in this specification, (meth)acrylate refers to both acrylate and methacrylate. Other similar terms are also the same.
[0034] In the molecular weight distribution (standard polystyrene conversion) of the (meth)acrylate polymer (A) of the present embodiment measured by gel permeation chromatography (GPC), the amount of components with a molecular weight of 3 million or more is 15% by mass or less, and the peak molecular weight (Mp) is 800,000 or more and 1.2 million or less. In addition, when the (meth)acrylate polymer (A) is dissolved in a mixed solvent of ethyl acetate and acetone containing 85% by mass of ethyl acetate so that the concentration is 20% by mass, the viscosity is 5000 mPa·s or more and 10000 mPa·s or less. In addition, the details of the GPC method and the method for measuring the viscosity are shown in the test examples described later.
[0035] Even when an adhesive sheet having an adhesive layer obtained from an adhesive composition P satisfying the above-mentioned physical properties is applied to an optical film such as a polarizing plate having an acrylic film (acrylic resin layer), the durability is still excellent. That is, even when a laminated body having an optical film with an adhesive layer formed by laminating the above-mentioned adhesive layer on the above-mentioned optical film is attached to an adherend such as a liquid crystal element (an alkali-free glass plate in the test example) and placed under high temperature conditions, hot and humid conditions, or thermal shock conditions, it is possible to suppress the occurrence of floating or peeling at the interface between the adhesive layer and the adherend.
[0036] In addition, the adhesive composition P that satisfies the above-mentioned physical property has good processability when applying the adhesive composition P. That is, the surface state of the adhesive layer obtained by applying the coating solution of the adhesive composition P is a high smooth state of the concave-convex etc. without vein shape (suzi shape). Therefore, it is possible to increase the coating speed, and seek to improve productivity. Even if this high smooth adhesive layer is applicable to the polaroid of filmization etc., the optical properties are still excellent.
[0037] From the perspective of the above-mentioned effects, in the molecular weight distribution of the (meth)acrylate polymer (A), the amount of the component with a molecular weight of 3,000,000 or more needs to be 15% by mass or less, preferably 13% by mass or less, more preferably 11% by mass or less, particularly preferably 10% by mass or less, and further preferably 9.0% by mass or less. If the amount of this component is 15% by mass or less, the surface smoothness of the obtained adhesive layer becomes higher, and excellent durability can be obtained.
[0038] The lower limit of the amount of the above-mentioned component may be 0 mass %, and is usually preferably 3 mass % or more, and particularly preferably 5 mass % or more.
[0039] The amount of the component having a molecular weight of 3,000,000 or more in the (meth)acrylate polymer (A) is not a parameter that can be determined simply by determining the monomer composition of the (meth)acrylate polymer (A), the weight average molecular weight (Mw) or the dispersity (Mw / Mn) (Mn is the number average molecular weight) of the (meth)acrylate polymer (A), but is an independent parameter that has no direct relationship with the monomer composition of the (meth)acrylate polymer (A), the weight average molecular weight (Mw) or the dispersity (Mw / Mn) of the (meth)acrylate polymer (A).
[0040] In addition, from the perspective of the above-mentioned effects, in the molecular weight distribution of the (meth)acrylate polymer (A), the peak molecular weight (Mp) needs to be 800,000 or more, preferably 850,000 or more, particularly preferably 900,000 or more, and further preferably 950,000 or more. If the peak molecular weight (Mp) is less than 800,000, the cohesive force of the obtained adhesive becomes too low, and the durability is reduced.
[0041] On the other hand, the peak molecular weight (Mp) needs to be 1.2 million or less, preferably 1.15 million or less, particularly preferably 1.1 million or less, and further preferably 1.05 million or less. If the peak molecular weight (Mp) exceeds 1.2 million, the durability of the resulting adhesive sheet is insufficient.
[0042] Furthermore, from the perspective of the above-mentioned effects, the viscosity of the (meth)acrylate polymer (A) needs to be 5000 mPa·s or more, preferably 6000 mPa·s or more, particularly preferably 7000 mPa·s or more, and further preferably 8000 mPa·s or more. If the above-mentioned viscosity is less than 5000 mPa·s, the cohesive force of the obtained adhesive is too low, and the durability is reduced.
[0043] On the other hand, the above-mentioned viscosity needs to be 10000mPa·s or less, preferably 9800mPa·s or less, particularly preferably 9500mPa·s or less, and further preferably 9200mPa·s or less. If the above-mentioned viscosity exceeds 10000mPa·s, the cohesive force of the obtained adhesive is too high, and the durability decreases. In addition, the surface state of the adhesive layer formed by coating becomes worse.
[0044] In the measurement of viscosity, when the (meth)acrylate polymer (A) dissolved in a solvent (polymerization solvent) is used, when the solvent is ethyl acetate and / or acetone, the respective amounts may be adjusted according to the polymerization solvent so that the mass ratio of ethyl acetate to acetone is 85:15. In addition, when the (meth)acrylate polymer (A) dissolved in a solvent (polymerization solvent) containing a solvent other than ethyl acetate and acetone is used, the solvent may be temporarily removed by evaporation and then redissolved in a mixed solvent of ethyl acetate and acetone (mass ratio 85:15).
[0045] Among them, the adhesive obtained by the adhesive composition P can be any one of an emulsion type, a solvent type and a solvent-free type, preferably a solvent type. At this time, it is preferred that the (meth)acrylate polymer (A) is polymerized by a solution polymerization method that is easy to control the molecular weight distribution. In addition, in the solution polymerization method, it is preferred not to use a solvent with a boiling point of 70°C or less as a polymerization solvent. Thus, when the adhesive composition P is applied, it is not easy to generate foaming in the coating solution, and the surface state of the obtained adhesive layer is a higher smooth state.
[0046] Examples of the solvent having a boiling point of 70° C. or lower include acetone, hexane, chloroform, diethyl ether, ethylene dichloride, tetrahydrofuran, methanol, pentane, and methyl acetate.
[0047] As the polymerization solvent that can be used for the polymerization of the (meth)acrylate polymer (A), for example, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, methyl ethyl ketone, etc. can be preferably listed, and two or more thereof can also be used simultaneously. Among them, ethyl acetate is preferably used from the viewpoints of compatibility with the monomer, boiling point, chain transfer during polymerization, etc.
[0048] In addition, as the polymerization solvent, a solvent having a boiling point exceeding 70° C. and a solvent having a boiling point below 70° C. may be mixed and used. For example, ethyl acetate and acetone may be mixed and used. In this case, the polymerization solvent preferably contains 80% by mass or more, particularly preferably 90% by mass or more, and further preferably 95% by mass or more of the solvent having a boiling point exceeding 70° C.
[0049] In the molecular weight distribution (standard polystyrene conversion) of the (meth) acrylate polymer (A) measured by the GPC method, the weight average molecular weight (Mw) is preferably 800,000 or more, particularly preferably 900,000 or more, and more preferably 1,000,000 or more. In addition, the weight average molecular weight (Mw) is preferably 2,000,000 or less, more preferably 1,700,000 or less, particularly preferably 1,500,000 or less, and more preferably 1,400,000 or less. By making the weight average molecular weight (Mw) of the (meth) acrylate polymer (A) within the above range, it is possible to prevent the durability from being reduced and suppress the surface state of the adhesive layer formed by coating from being deteriorated.
[0050] Furthermore, by making the weight average molecular weight (Mw) of the (meth)acrylate polymer (A) within the above range and making the gel fraction of the adhesive described later within a predetermined range, even when the obtained adhesive layer is applied to an optical film such as a polarizing plate having an acrylic film (acrylic resin layer), the re-operability is excellent. That is, after the optical film with an adhesive layer formed by laminating the adhesive layer on the optical film is attached to an adherend such as a liquid crystal element (an alkali-free glass plate in the test example), when the optical film with an adhesive layer is peeled off from the adherend (the optical film with an adhesive layer is re-operated), the acrylic resin layer can be well peeled off without breaking.
[0051] In the molecular weight distribution (standard polystyrene conversion) of the (meth)acrylate polymer (A) measured by the GPC method, the dispersion (Mw / Mn) is preferably 1.5 or more, more preferably 2.0 or more, particularly preferably 2.5 or more, and further preferably 3.0 or more. In addition, the dispersion (Mw / Mn) is preferably 5.0 or less, more preferably 4.5 or less, particularly preferably 4.0 or less, and further preferably 3.8 or less. By making the dispersion (Mw / Mn) of the (meth)acrylate polymer (A) within the above range, the cohesive force of the obtained adhesive becomes moderate, and more excellent durability can be obtained.
[0052] 1. Each ingredient
[0053] (1) (Meth)acrylate polymer (A)
[0054] The (meth)acrylate polymer (A) of the present embodiment is not limited as long as it satisfies the above-mentioned physical properties. As monomers constituting the polymer, it is preferred to contain at least (meth)acrylate alkyl ester and a reactive functional group-containing monomer having a reactive functional group in the molecule. By containing (meth)acrylate alkyl ester as a component monomer, good adhesion can be exhibited. In addition, by containing a reactive functional group-containing monomer as a component monomer, the reactive functional group from the reactive functional group-containing monomer reacts with the crosslinking agent (B) described later, thereby forming a crosslinked structure (three-dimensional network structure), and obtaining an adhesive having a predetermined cohesive force.
[0055] The alkyl group of the above-mentioned alkyl (meth)acrylate may be linear or branched. As the alkyl (meth)acrylate, from the viewpoint of adhesiveness, the alkyl (meth)acrylate having 1 to 20 carbon atoms in the alkyl group is preferred. As the alkyl (meth)acrylate having 1 to 20 carbon atoms in the alkyl group, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearic (meth)acrylate, etc. can be cited.
[0056] Among the above esters, from the viewpoint of effectively imparting adhesive force and easily obtaining the above physical properties, (meth) alkyl acrylates having an alkyl group with 1 to 12 carbon atoms are more preferred, and alkyl acrylates having an alkyl group with 1 to 8 carbon atoms are particularly preferred. Specifically, methyl (meth) acrylate, n-butyl (meth) acrylate, and 2-ethylhexyl (meth) acrylate are preferably listed, and methyl (meth) acrylate and n-butyl (meth) acrylate are more preferably listed. These esters may be used alone or in combination of two or more.
[0057] From the viewpoint of imparting adhesiveness, the (meth)acrylate polymer (A) preferably contains 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 85% by mass or more of the above-mentioned alkyl (meth)acrylate as a monomer unit constituting the polymer. From the viewpoint of ensuring the blending amount of other components, it is preferably 99% by mass or less, more preferably 95% by mass or less, and particularly preferably 90% by mass or less of the above-mentioned alkyl (meth)acrylate.
[0058] Preferred examples of the reactive functional group-containing monomer contained in the (meth)acrylate polymer (A) as a monomer unit constituting the polymer include a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. These reactive functional group-containing monomers may be used alone or in combination of two or more.
[0059] Among the above-mentioned reactive functional group-containing monomers, hydroxyl group-containing monomers and carboxyl group-containing monomers are preferred, and the use of both of them is particularly preferred. This allows a good crosslinking structure to be formed in the adhesive, and the resulting adhesive sheet has better durability and reworkability.
[0060] Examples of hydroxyl-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the perspective of reactivity with a crosslinking agent. These hydroxyl-containing monomers may be used alone or in combination of two or more.
[0061] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred from the perspective of the adhesive force of the resulting (meth)acrylate polymer (A). These carboxyl-containing monomers may be used alone or in combination of two or more.
[0062] The (meth)acrylate polymer (A) preferably contains 0.5% by mass or more, particularly preferably 1.0% by mass or more, and further preferably 1.3% by mass or more of a reactive functional group-containing monomer as a monomer unit constituting the polymer. In addition, the (meth)acrylate polymer (A) preferably contains 5.0% by mass or less, particularly preferably 4.0% by mass or less, and further preferably 3.0% by mass or less of a reactive functional group-containing monomer as a monomer unit constituting the polymer. By making the content of the reactive functional group-containing monomer within the above range, the cohesive force of the obtained adhesive becomes moderate, and more excellent durability and reoperability can be obtained.
[0063] In addition, when (meth) acrylate polymer (A) contains hydroxyl-containing monomer as the monomer unit constituting the polymer, the content of hydroxyl-containing monomer is preferably more than 0.1% by mass, particularly preferably more than 0.5% by mass. In addition, the content of the hydroxyl-containing monomer is preferably less than 5.0% by mass, particularly preferably less than 3.0% by mass, and more preferably less than 2.0% by mass. On the other hand, when (meth) acrylate polymer (A) contains carboxyl-containing monomer as the monomer unit constituting the polymer, the content of carboxyl-containing monomer is preferably more than 0.1% by mass, particularly preferably more than 0.3% by mass. In addition, the content of the carboxyl-containing monomer is preferably less than 3.0% by mass, particularly preferably less than 2.0% by mass, and more preferably less than 1.0% by mass. By making the contents of hydroxyl-containing monomer and carboxyl-containing monomer respectively as above, a good cross-linked structure can be formed to obtain more excellent durability and reoperability.
[0064] The (meth)acrylate polymer (A) of this embodiment preferably further contains an aromatic ring-containing monomer having an aromatic ring in the molecule as a monomer constituting the polymer. By containing an aromatic ring-containing monomer as a component monomer, the cohesive force of the obtained adhesive is more appropriate and better durability can be obtained.
[0065] As the aromatic ring-containing monomer, a (meth)acrylate having an aromatic ring is preferred. Examples of the aromatic ring include a benzene ring, a naphthalene ring, an anthracene ring, a biphenyl ring, and a fluorene ring, and among them, a benzene ring is preferred.
[0066] As the aromatic ring-containing monomer, for example, phenyl (meth)acrylate, 2-phenylethyl (meth)acrylate, benzyl (meth)acrylate, naphthyl (meth)acrylate; phenoxyalkyl (meth)acrylates such as phenoxyethyl (meth)acrylate and phenoxybutyl (meth)acrylate; (meth)acrylates containing aromatic rings and ethylene glycol such as phenyl diethylene glycol (meth)acrylate and phenoxydiethylene glycol (meth)acrylate; ethoxylated o-phenylphenol acrylate, ethylene oxide-modified cresol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, etc. Among them, from the point of view of cohesion, phenoxyalkyl (meth)acrylates and (meth)acrylates containing aromatic rings and ethylene glycol are preferred, phenoxyethyl (meth)acrylate and phenyl diethylene glycol (meth)acrylate are particularly preferred, and phenyl diethylene glycol (meth)acrylate is further preferred. These aromatic ring-containing monomers can be used alone or in combination of two or more.
[0067] The (meth)acrylate polymer (A) preferably contains 2.0% by mass or more, particularly preferably 3.0% by mass or more, and further preferably 5.0% by mass or more of an aromatic ring-containing monomer as a monomer unit constituting the polymer. In addition, the (meth)acrylate polymer (A) preferably contains 20.0% by mass or less, particularly preferably 15.0% by mass or less, and further preferably 12.0% by mass or less of an aromatic ring-containing monomer as a monomer unit constituting the polymer. By making the content of the aromatic ring-containing monomer within the above range, the cohesive force of the obtained adhesive is more appropriate, and more excellent durability can be obtained.
[0068] The (meth)acrylate polymer (A) may contain a nitrogen atom-containing monomer as a monomer unit constituting the polymer. Examples of the nitrogen atom-containing monomer include monomers having an amino group, monomers having an amide group, monomers having a nitrogen-containing heterocycle, and the like. Among them, from the perspective of the durability and reoperability of the resulting adhesive, monomers having an amide group (amide-containing monomers) are preferred. These nitrogen atom-containing monomers may be used alone or in combination of two or more. In addition, the above-mentioned reactive functional group-containing monomers are not included in the so-called nitrogen atom-containing monomers herein.
[0069] Examples of the amide group-containing monomer include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, and alkoxyalkyl(meth)acrylamide such as N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide. Among them, alkoxyalkyl(meth)acrylamide is preferred, N-butoxyalkyl(meth)acrylamide is particularly preferred, and N-butoxymethyl(meth)acrylamide is further preferred from the perspective of durability and reworkability of the resulting adhesive.
[0070] When the (meth)acrylate polymer (A) contains a nitrogen atom-containing monomer (particularly an amide-containing monomer) as a monomer unit constituting the polymer, the content is preferably 0.01% by mass or more, particularly preferably 0.2% by mass or more, and further preferably 0.5% by mass or more. In addition, the content is preferably 5.0% by mass or less, particularly preferably 3.0% by mass or less, and further preferably 2.0% by mass or less. By making the content of the nitrogen atom-containing monomer (particularly an amide-containing monomer) within the above range, the durability of the resulting adhesive is more excellent.
[0071] The polymerization form of the (meth)acrylate polymer (A) may be a random copolymer or a block copolymer.
[0072] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.
[0073] The content of the (meth)acrylate polymer (A) in the adhesive composition P of the present embodiment is preferably 80% by mass or more, particularly preferably 85% by mass or more, and more preferably 90% by mass or more. In addition, the content of the (meth)acrylate polymer (A) is preferably 99.9% by mass or less, particularly preferably 99.7% by mass or less, and more preferably 99.5% by mass or less. By making the content of the (meth)acrylate polymer (A) within the above range, the durability of the obtained adhesive is more excellent.
[0074] (2) Cross-linking agent (B)
[0075] By heating the adhesive composition P, the crosslinking agent (B) crosslinks the (meth)acrylate polymer (A) to form a good three-dimensional network crosslinking structure. This can provide an adhesive having a predetermined cohesive force and having better durability and reworkability.
[0076] As the above-mentioned crosslinking agent (B), as long as it is a component that reacts with the reactive functional group possessed by the (meth) acrylate polymer (A), for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. can be listed. Among them, when the (meth) acrylate polymer (A) contains a hydroxyl-containing monomer as a component monomer unit, as the crosslinking agent (B), it is preferred to use an isocyanate crosslinking agent with excellent reactivity with a hydroxyl group. In addition, when the (meth) acrylate polymer (A) contains a hydroxyl-containing monomer and a carboxyl-containing monomer as a component monomer unit, it is also preferred to use an isocyanate crosslinking agent. In addition, the crosslinking agent (B) can be used alone or in combination of two or more.
[0077] The isocyanate crosslinking agent contains at least a polyisocyanate compound. As the polyisocyanate compound, for example, aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, and biuret bodies and isocyanurate bodies of these polyisocyanate compounds, and adducts thereof as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil, etc. Among them, from the perspective of reactivity and durability with the (meth) acrylate polymer (A), trimethylolpropane-modified aromatic polyisocyanates and isocyanurate bodies of aliphatic polyisocyanates are preferred, and trimethylolpropane-modified toluene diisocyanate and hexamethylene diisocyanate-based isocyanurates are particularly preferred.
[0078] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more, based on the lower limit. In addition, the content is preferably 1.0 parts by mass or less, particularly preferably 0.8 parts by mass or less, and more preferably 0.5 parts by mass or less, based on the upper limit. If the content of the crosslinking agent (B) is within the above range, a prescribed crosslinked structure can be formed, and the durability and reoperability of the resulting adhesive are more excellent.
[0079] (3) Silane coupling agent (C)
[0080] The adhesive composition P preferably further contains a silane coupling agent (C). Thereby, regardless of whether the adherend is a plastic plate or a glass member, the adhesive strength to the adherend is improved and the durability is further improved.
[0081] As the silane coupling agent (C), an organosilicon compound having good compatibility with the (meth)acrylate polymer (A), light-transmitting properties and having at least one alkoxysilyl group in the molecule is preferred.
[0082] Examples of the silane coupling agent (C) include silicon compounds containing polymerizable unsaturated groups such as vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane, silicon compounds having epoxy structures such as 3-glycidoxypropyl trimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, and silicon compounds containing 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl dimethoxymethylsilane. Amino group silicon compounds such as mercapto silicon compounds, 3-aminopropyl trimethoxysilane, N-(2-aminoethyl)-3-aminopropyl trimethoxysilane, N-(2-aminoethyl)-3-aminopropyl methyl dimethoxysilane, 3-chloropropyl trimethoxysilane, isocyanate propyl triethoxysilane, or condensates of at least one of these components with methyl triethoxysilane, ethyl triethoxysilane, methyl trimethoxysilane, ethyl trimethoxysilane, etc. These silane coupling agents may be used alone or in combination of two or more.
[0083] From the viewpoint of durability, the content of the silane coupling agent (C) in the adhesive composition P is preferably 0.05 parts by mass or more, particularly preferably 0.1 parts by mass or more, and further preferably 0.3 parts by mass or more, relative to 100 parts by mass of the (meth)acrylate polymer (A). In addition, from the viewpoint of adhesion, the content is preferably 5.0 parts by mass or less, particularly preferably 2.0 parts by mass or less, and further preferably 1.0 parts by mass or less.
[0084] (4) Various additives
[0085] Various additives commonly used in acrylic adhesives may be added to the adhesive composition P as needed, such as antistatic agents, dispersants (e.g., alkylene glycol dialkyl ethers), tackifiers, antioxidants, ultraviolet absorbers, light stabilizers, softeners, fillers, refractive index adjusters, etc. The adhesive composition P represents a mixture of various components that remain in the adhesive layer as they are or in a reacted state, and components removed in a drying process, such as a polymerization solvent or a dilution solvent described later, are not included in the adhesive composition P.
[0086] Examples of the antistatic agent include ionic compounds, anionic surfactants, alkali metal salts, cationic surfactants, and nonionic surfactants. Among them, it is preferred to use at least one selected from ionic compounds and alkali metal salts.
[0087] As the ionic compound, nitrogen-containing onium salts, sulfur-containing onium salts, phosphorus-containing onium salts, etc. are preferred. In addition, as alkali metal salts, lithium salts, potassium salts, etc. are preferred. These ionic compounds can be used alone or in combination of two or more. Among the above-mentioned ionic compounds, nitrogen-containing onium salts are preferred, and ionic compounds of nitrogen-containing onium salts are particularly preferred, and pyridinium salt-based ionic compounds are further preferred. By using these ionic compounds, antistatic performance can be exhibited without reducing durability.
[0088] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the antistatic agent in the adhesive composition P is preferably 0.5 parts by mass or more, particularly preferably 1.0 parts by mass or more, and further preferably 2.0 parts by mass or more. In addition, the content is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, particularly preferably 5.0 parts by mass or less, and further preferably 3.5 parts by mass or less. By making the content of the antistatic agent within the above range, the balance of the durability of the antistatic performance and the adhesive becomes good.
[0089] 2. Preparation method of adhesive composition
[0090] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), and mixing the obtained (meth)acrylate polymer (A), a crosslinking agent (B), and, if necessary, a silane coupling agent (C), additives, and the like.
[0091] The (meth)acrylate polymer (A) can be prepared by polymerizing a mixture of monomer units constituting the polymer using a conventional free radical polymerization method. As described above, the (meth)acrylate polymer (A) is preferably polymerized by a solution polymerization method. The polymerization solvent used in the solution polymerization method is as described above.
[0092] In the above-mentioned solution polymerization method, a polymerization initiator can be used as needed. As the polymerization initiator, azo compounds, organic peroxides, etc. can be listed, and two or more kinds can also be used simultaneously. As azo compounds, for example, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl azobisisobutyrate, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobis[2-(2-imidazoline-2-yl)propane], etc. can be listed.
[0093] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxy)ethyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0094] Furthermore, in the above-mentioned polymerization step, by blending a chain transfer agent such as 2-mercaptoethanol, the molecular weight distribution of the obtained polymer can be adjusted.
[0095] After the (meth)acrylate polymer (A) is obtained, a crosslinking agent (B) and, if necessary, a silane coupling agent (C), additives, a diluting solvent, etc. are added to the solution of the (meth)acrylate polymer (A) and the mixture is thoroughly mixed to obtain a solvent-diluted adhesive composition P (coating solution).
[0096] As a diluting solvent for diluting the adhesive composition P to prepare a coating solution, it is preferred not to use a solvent having a boiling point of 70° C. or less. As a result, when the adhesive composition P is applied, bubbles are less likely to occur in the coating solution, and the surface state of the obtained adhesive layer is a smoother state. The solvent having a boiling point of 70° C. or less is the solvent described above as the polymerization solvent.
[0097] As the diluent solvent that can be used, for example, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, methyl ethyl ketone, etc. can be preferably mentioned, and two or more kinds can be used at the same time. Among them, ethyl acetate is preferably used from the viewpoint of the surface state of the obtained adhesive layer.
[0098] In addition, as the dilution solvent, a solvent having a boiling point exceeding 70° C. and a solvent having a boiling point below 70° C. may be mixed and used. For example, ethyl acetate and acetone may be mixed and used. In this case, the dilution solvent preferably contains 90% by mass or more, particularly preferably 95% by mass or more, and further preferably 98% by mass or more of the solvent having a boiling point exceeding 70° C.
[0099] The concentration and viscosity of the coating solution prepared in the above manner are not particularly limited as long as they are within the range that can be coated, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted in a manner such that the concentration is 10 to 40% by mass. In addition, when obtaining the coating solution, it is not necessary to add a diluting solvent, etc. As long as the adhesive composition P has a viscosity that can be coated, a diluting solvent may not be added. At this time, the adhesive composition P is a coating solution in which the polymerization solvent of the (meth)acrylate polymer (A) is directly used as the diluting solvent.
[0100] [Adhesive]
[0101] The adhesive of this embodiment is formed by crosslinking the above-mentioned adhesive composition P. The crosslinking of the adhesive composition P can be preferably performed by heat treatment. In addition, the drying treatment when the diluting solvent of the applied adhesive composition P is volatilized can also be used as the heating treatment.
[0102] When heat treatment is performed, the heating temperature is preferably 50 to 150° C., particularly preferably 70 to 120° C. In addition, the heating time is preferably 30 seconds to 10 minutes, particularly preferably 50 seconds to 2 minutes. After the heat treatment, a aging period of about 1 to 2 weeks can be set at room temperature (e.g., 23° C., 50% RH) as needed. When the aging period is required, an adhesive layer with specified physical properties is formed after the aging period, and when the aging period is not required, an adhesive layer with specified physical properties is formed after the heat treatment is completed.
[0103] Through the above-mentioned heat treatment (and aging), the (meth)acrylate polymer (A) is cross-linked by the cross-linking agent (B) to form a three-dimensional network structure.
[0104] The gel fraction of the adhesive of the present embodiment is preferably 50% or more, more preferably 60% or more, particularly preferably 70% or more, and further preferably 72% or more. In addition, the above-mentioned gel fraction is preferably 95% or less, particularly preferably 85% or less, and further preferably 80% or less. When the gel fraction of the adhesive is within the above-mentioned range, by making the weight average molecular weight (Mw) of the (meth)acrylate polymer (A) within the above-mentioned range, the durability and reoperability of the obtained adhesive layer become excellent. In addition, the method for measuring the gel fraction in this specification is shown in the test example described later.
[0105] [Adhesive sheet]
[0106] The adhesive sheet of the present embodiment has an adhesive layer formed by the above-mentioned adhesive. A release sheet can be laminated on one or both sides of the adhesive layer. In addition, a release sheet can be laminated on one side of the adhesive layer, and a required substrate can be laminated on the other side. In addition, when the substrate is an optical film, in this specification, the adhesive sheet is equivalent to the optical film with an adhesive layer described later.
[0107] The thickness of the adhesive layer can be appropriately determined according to the purpose of use of the adhesive sheet, but is preferably 5 μm or more, particularly preferably 10 μm or more, and more preferably 15 μm or more. In addition, the thickness of the adhesive layer is preferably 50 μm or less, particularly preferably 40 μm or less, and more preferably 30 μm or less. By making the thickness of the adhesive layer within the above range, when it is applied to an optical film such as a polarizing plate having an acrylic resin layer, the durability and reoperability are more excellent.
[0108] As the release sheet, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate film, ionomer resin film, ethylene-(methyl) acrylic acid copolymer film, ethylene-(methyl) acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, etc. can be used. In addition, crosslinked films of these films can also be used. Further, laminated films of these films can be used.
[0109] It is preferred that at least one surface of the release sheet (particularly the release surface in contact with the adhesive layer) is subjected to a release treatment. Examples of release agents used for the release treatment include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax release agents. In addition, the release surface of the release sheet in this specification refers to a surface of the release sheet that has release properties, and also includes any of a surface subjected to a release treatment and a surface that has not been subjected to a release treatment but exhibits release properties.
[0110] When release sheets are laminated on both surfaces of the adhesive layer, it is preferred that one release sheet be a heavy release sheet having a large release force and the other release sheet be a light release sheet having a small release force.
[0111] The thickness of the release sheet is not particularly limited, but is generally about 20 to 150 μm.
[0112] As the substrate, there is no particular limitation, and all materials commonly used as the substrate sheet of the adhesive sheet can be used. For example, in addition to the required optical film, woven or non-woven fabrics using fibers such as rayon, acrylic acid, and polyester can be listed; synthetic paper; paper such as offset paper (high-quality paper), glassine, impregnated paper, and coated paper; metal foils such as aluminum and copper; foams such as polyurethane foam and polyethylene foam; polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyurethane films, polyethylene films, polypropylene films, cellulose films such as triacetyl cellulose, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene-vinyl acetate copolymer films, polystyrene films, polycarbonate films, acrylic resin films, norbornene resin films, cycloolefin resin films, etc.; laminates of two or more of these substrates, etc. The plastic film can be a plastic film that has been stretched uniaxially or biaxially.
[0113] The thickness of the substrate varies depending on its type, but is usually 5 to 500 μm, preferably 10 to 300 μm, and particularly preferably 20 to 150 μm.
[0114] As an example of a method for manufacturing an adhesive sheet of the present embodiment, a coating solution of an adhesive composition P is applied to the release surface of a release sheet, and a heat treatment is performed to form a coating film. After that, another release sheet (so that the release surface is in contact with the coating film) or a substrate is stacked on the coating film as needed. When a maturation period is not required, the coating film directly becomes an adhesive layer, and when a maturation period is required, the coating film becomes an adhesive layer after the maturation period. The conditions for heat treatment and maturation are as described above.
[0115] As a method for applying the coating solution, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, or the like can be used.
[0116] Since the adhesive composition P in this embodiment has good processability during coating, a highly smooth adhesive layer can be formed even if the coating speed is increased. In particular, when a solvent having a boiling point of 70° C. or less such as acetone is not used as the polymerization solvent for the (meth)acrylate polymer (A), it is difficult to generate bubbles in the coating solution, so the obtained adhesive layer becomes smoother.
[0117] [Optical film with adhesive layer]
[0118] The optical film with an adhesive layer of the present embodiment comprises an optical film having at least one acrylic resin layer and an adhesive layer laminated on at least one surface of the optical film. The adhesive layer is formed by the adhesive of the present embodiment described above, or is formed by the adhesive layer of the adhesive sheet of the present embodiment described above. The thickness of the adhesive layer is the same as that of the adhesive layer of the adhesive sheet described above.
[0119] The acrylic resin layer in the optical film having at least one acrylic resin layer is preferably present at a position in contact with the adhesive layer. In addition, the acrylic resin layer may be an acrylic resin layer formed by extrusion molding. In addition, the "acrylic resin layer formed by extrusion molding" also includes an acrylic resin layer obtained by stretching after extrusion molding.
[0120] In an optical film having at least one acrylic resin layer, although the acrylic resin layer has the characteristic of being prone to brittle fracture, when the acrylic resin layer of the optical film comes into contact with the above-mentioned adhesive layer, the adhesion of the adhesive layer to the acrylic resin layer is still high, and it is not easy to float or peel off on the surface under durable conditions such as high temperature conditions, hot and humid conditions, and thermal shock conditions, and the durability is excellent.
[0121] The optical film can be formed by a single layer (acrylic resin layer) or by multiple layers. As the optical film, for example, a polarizer, a polarizer, a phase difference plate, a composite polarizer such as a polarizer with a phase difference plate, a field angle compensation film, a brightness enhancement film, a contrast enhancement film, a liquid crystal polymer film, a diffusion film, a semi-transmissive reflective film, a laminate of these films, etc. can be listed. Among them, since the polarizer is easy to shrink, the size change is large, and durability is required, the optical film containing the polarizer is suitable as the optical film of the optical film with an adhesive layer of the present embodiment.
[0122] Reference Figure 1 , an example of an optical film with an adhesive layer according to this embodiment when the optical film is a polarizing plate is described. Figure 1 As shown, the optical film 10 with an adhesive layer of this embodiment includes a polarizing plate 2 and a laminated film on one surface of the polarizing plate 2 (on the Figure 1 In addition, although not shown, a release sheet may be laminated on the surface of the adhesive layer 1 opposite to the polarizer 2 side until the optical film 10 with an adhesive layer is used.
[0123] The adhesive layer 1 is formed of the adhesive of the present embodiment described above.
[0124] The polarizing plate 2 of this embodiment includes a polarizer 21, and a Figure 1 The first protective layer 22 is stacked on the upper side of the polarizer 21, and the other side of the polarizer 21 is stacked on the upper side of the polarizer 21. Figure 1 The first protective layer 22 and the second protective layer 23 function as polarizer protective layers for protecting the polarizer 21.
[0125] As an example, the polarizer 21 is preferably formed of a polyvinyl alcohol resin film on which a dichroic dye such as iodine is adsorbed and oriented. The polarizer 21 is preferably manufactured through the following steps: a step of uniaxially stretching the polyvinyl alcohol resin film; a step of dyeing the polyvinyl alcohol resin film with a dichroic dye to adsorb the dichroic dye; and a step of treating the polyvinyl alcohol resin film adsorbing the dichroic dye with a boric acid aqueous solution.
[0126] The thickness of the polarizer 21 is preferably about 3 to 50 μm, particularly preferably about 10 to 30 μm.
[0127] Either or both of the first protective layer 22 and the second protective layer 23 are acrylic resin layers containing acrylic resin as a main component. The first protective layer 22 and the second protective layer 23 are preferably formed of a transparent resin film. The first protective layer 22 and the second protective layer 23 may be formed of the same type of transparent resin film or of different types of transparent resin films. The transparent resin film may be an unstretched film or a uniaxially stretched or biaxially stretched film.
[0128] In addition, the first protective layer 22 or the second protective layer 23 may be a zero phase difference film or a phase difference film. In addition, the zero phase difference film refers to an in-plane phase difference (retardaion) R e Retardation R in the thickness direction th The retardation film refers to the in-plane retardation R e and the phase difference R in the thickness direction th A film having at least one phase difference value of -15 to 15 nm.
[0129] As an example of the acrylic resin forming the acrylic resin layer, a polymer having methacrylate as a main monomer is preferred, and a copolymer obtained by copolymerizing the polymer with a small amount of other comonomer components is more preferred. The copolymer can usually be obtained by polymerizing a monofunctional monomer containing methacrylate or acrylate in the presence of a free radical polymerization initiator and a chain transfer agent. In addition, a third monofunctional monomer may be copolymerized in the acrylic resin.
[0130] The acrylic resin layer may contain known additives as required, for example, a UV absorber. In addition, from the perspective of film forming properties and impact resistance of the film, the acrylic resin layer may contain acrylic rubber particles as an impact modifier.
[0131] As a method for producing the transparent resin film (acrylic resin film), any method such as a melt casting method, a melt extrusion method such as a T-die method or an inflation method, and a calendering method can be used.
[0132] When either the first protective layer 22 or the second protective layer 23 is an acrylic resin layer, the other protective layer may be a resin layer (transparent resin film) mainly composed of polyester resin, polycarbonate resin, amorphous polyolefin resin, cellulose resin, etc.
[0133] The thickness of the first protective layer 22 and the second protective layer 23 is usually in the range of about 5 to 200 μm, preferably 10 to 120 μm, particularly preferably 10 to 85 μm, and further preferably 30 to 70 μm.
[0134] The polarizer 21 and the first protective layer 22, and the polarizer 21 and the second protective layer 23 can be bonded and laminated using an adhesive. As the adhesive, an appropriate and suitable adhesive can be used according to the type or purpose of the adherend. For example, solvent-based adhesives, emulsion-based adhesives, water-based adhesives, pressure-sensitive adhesives, re-moistening adhesives, condensation-type adhesives, solvent-free adhesives, film-like adhesives, hot-melt adhesives, etc. can be listed. Among the above-mentioned adhesives, water-based adhesives are preferred. As representative examples thereof, water-based adhesives containing polyvinyl alcohol resins or water-soluble epoxy resins can be listed.
[0135] The fracture stress measured according to JIS K7127:1999 (wherein the width of the test piece is 50 mm) of the optical film (especially polarizer) of the present embodiment is preferably 10N / 50mm width or less, particularly preferably 5N / 50mm width or less, and more preferably 3.5N / 50mm width or less. According to the adhesive layer of the present embodiment, even when attached to an optical film (polarizer) with a small fracture stress as described above and used, the optical film can be peeled off (reoperated) from an adherend such as a liquid crystal element without breaking the optical film. On the other hand, from the perspective of strength, the lower limit of the fracture stress of the optical film of the present embodiment is preferably 0.1N / 50mm width or more, particularly preferably 1N / 50mm width or more, and more preferably 2N / 50mm width or more. In addition, the fracture stress of this specification is a value that does not depend on the thickness of the optical film, and for an optical film of any thickness, it is a value obtained by measuring under the condition of a width of 50 mm. The details of the above-mentioned fracture stress determination method are shown in the embodiments described below.
[0136] In addition, the heat shrinkage rate of the optical film (especially polarizer) of this embodiment in the direction most susceptible to heat shrinkage after being placed in an environment of 85°C for 144 hours is preferably 0.5% or more, particularly preferably 1.3% or more, and further preferably 1.8% or more. According to the adhesive layer of this embodiment, even when it is attached to an optical film (polarizer) with a large heat shrinkage rate as described above and used, the durability is still excellent, and even when placed under high temperature conditions, hot and humid conditions, or thermal shock conditions, it is possible to suppress floating or peeling on the surface of the adhesive layer and the adherend. On the other hand, the upper limit of the heat shrinkage rate of the optical film of this embodiment is preferably 10% or less, particularly preferably 5% or less, and further preferably 3% or less.
[0137] The thermal shrinkage rate is represented by the following formula, and the details of a specific measurement method are shown in Examples described later.
[0138] S[%]={(M1-M2) / M1}×100
[0139] M1: The length of one side before heating
[0140] M2: length of one side after heating
[0141] The size of the sample to be measured: 10cm×10cm
[0142] Heating conditions: 85°C, 144 hours
[0143] As an example of a method for manufacturing an optical film 10 with an adhesive layer, as the adhesive sheet of the present embodiment described above, an adhesive sheet having release sheets laminated on both sides of an adhesive layer is prepared, and one release sheet (light release type release sheet) is peeled off. Then, the second acrylic resin layer 23 of the polarizer 2 is overlapped on the exposed adhesive layer, and the adhesive sheet and the polarizer 2 are pressed and bonded. Thus, the optical film 10 with an adhesive layer (with release sheet) described above is obtained.
[0144] As another example of the method for producing the optical film 10 with an adhesive layer, a solution (coating solution) containing the adhesive composition P is applied to the release surface of a release sheet, and after heat treatment to form a coating film, the second acrylic resin layer 23 of the polarizer 2 is overlapped on the coating film. When a ripening period is required, the coating film becomes the adhesive layer 1 by setting the ripening period, and when a ripening period is not required, the coating film directly becomes the adhesive layer 1. Thus, the optical film 10 with an adhesive layer (with a release sheet) is obtained.
[0145] By using the optical film 10 with an adhesive layer, for example, a liquid crystal display device including a liquid crystal element and a polarizing plate can be manufactured.
[0146] Specifically, the adhesive layer of the optical film 10 with an adhesive layer (when a release sheet is laminated, the adhesive layer exposed by peeling off the release sheet) is superimposed on a desired surface of the liquid crystal cell and pressure-bonded. Thus, a liquid crystal display device including a liquid crystal cell and a polarizing plate 2 is obtained.
[0147] Since the adhesive layer 1 of the optical film 10 with an adhesive layer of the present embodiment has excellent durability, even if the obtained liquid crystal display device is placed under high temperature conditions, hot and humid conditions, or thermal shock conditions, it is possible to suppress the occurrence of floating or peeling at the interface of the adhesive layer 1. For example, even if a glass plate to which the optical film 10 with an adhesive layer is attached is placed under high temperature conditions of 80°C or hot and humid conditions of 60°C and 90% RH for 250 hours, or is subjected to a thermal shock of -35°C to 70°C (30 minutes each, 200 cycles), it is possible to suppress the occurrence of floating or peeling.
[0148] In addition, when the gel fraction of the adhesive of the adhesive layer 1 of the optical film 10 with an adhesive layer of the present embodiment and the weight average molecular weight (Mw) of the (meth) acrylate polymer (A) are within the specified range, excellent reoperability can be obtained. At this time, when the optical film 10 with an adhesive layer temporarily attached to the liquid crystal element is peeled off, the polarizer 2 (acrylic resin layers 22, 23) of the optical film 10 with an adhesive layer can be suppressed from breaking.
[0149] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes or equivalents within the technical scope of the present invention.
[0150] Example
[0151] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.
[0152] [Preparation Example 1] (Preparation of (meth)acrylate polymer (A-1))
[0153] Using ethyl acetate as a polymerization solvent, 78.4 parts by mass of n-butyl acrylate, 10 parts by mass of methyl acrylate, 10 parts by mass of phenoxyethyl acrylate, 1 part by mass of 2-hydroxyethyl acrylate, and 0.6 parts by mass of acrylic acid were copolymerized to prepare a (meth)acrylate polymer (A-1).
[0154] [Preparation Example 2] (Preparation of (meth)acrylate polymer (A-2))
[0155] A mixed solvent of ethyl acetate and acetone (mass ratio 80:20) was used as a polymerization solvent, and 78.4 parts by mass of n-butyl acrylate, 10 parts by mass of methyl acrylate, 10 parts by mass of phenoxyethyl acrylate, 1 part by mass of 2-hydroxyethyl acrylate and 0.6 parts by mass of acrylic acid were copolymerized to prepare a (meth)acrylate polymer (A-2).
[0156] [Preparation Example 3] (Preparation of (meth)acrylate polymer (A-3))
[0157] Using ethyl acetate as a polymerization solvent, 68.0 parts by mass of n-butyl acrylate, 20 parts by mass of methyl acrylate, 10 parts by mass of phenyl diethylene glycol acrylate, 0.6 parts by mass of N-butoxymethyl acrylamide, 1 part by mass of 2-hydroxyethyl acrylate and 0.4 parts by mass of acrylic acid were copolymerized to prepare a (meth)acrylate polymer (A-3).
[0158] [Preparation Example 4] (Preparation of (meth)acrylate polymer (A-4))
[0159] A mixed solvent of ethyl acetate and acetone (mass ratio 80:20) was used as a polymerization solvent, and 68.0 parts by mass of n-butyl acrylate, 20 parts by mass of methyl acrylate, 10 parts by mass of phenyl diethylene glycol acrylate, 0.6 parts by mass of N-butoxymethyl acrylamide, 1 part by mass of 2-hydroxyethyl acrylate and 0.4 parts by mass of acrylic acid were copolymerized to prepare a (meth)acrylate polymer (A-4).
[0160] [Preparation Example 5] (Preparation of (meth)acrylate polymer (A-5))
[0161] Using ethyl acetate as a polymerization solvent, 67.5 parts by mass of n-butyl acrylate, 20 parts by mass of methyl acrylate, 10 parts by mass of phenyl diethylene glycol acrylate, 1 part by mass of 2-hydroxyethyl acrylate and 1.5 parts by mass of acrylic acid were copolymerized to prepare a (meth)acrylate polymer (A-5).
[0162] In addition, the details of the abbreviations and the like described in Table 1 are as follows.
[0163] [Composition of (meth)acrylate polymer]
[0164] BA: n-butyl acrylate
[0165] MA: Methyl acrylate
[0166] PEA: Phenoxyethyl acrylate
[0167] PEA2: Phenyl diethylene glycol acrylate
[0168] BMAA: N-Butoxymethylacrylamide
[0169] HEA: 2-Hydroxyethyl Acrylate
[0170] AA: Acrylic acid
[0171] [Example 1]
[0172] 1. Manufacturing of polarizers
[0173] (1) Production of polarizing filter
[0174] A polyvinyl alcohol film having an average degree of polymerization of about 2,400 and a saponification degree of 99.9 mol% or more and having a thickness of 60 μm, formed of polyvinyl alcohol, was uniaxially stretched to about 5 times by a dry method, and further immersed in pure water at 60°C for 1 minute while maintaining the tension. Then, it was immersed in an aqueous solution having a mass ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 at 28°C for 60 seconds. Next, it was immersed in an aqueous solution having a mass ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 at 72°C for 300 seconds. Then, after washing with pure water at 26°C for 20 seconds, it was dried at 65°C to obtain a polarizer in which iodine was adsorbed and oriented in polyvinyl alcohol. The thickness of the polarizer was 23 μm.
[0175] (2) Preparation of polarizer
[0176] 3 parts by mass of carboxyl-modified polyvinyl alcohol (KURARAY CO., LTD., trade name "KL-318") was dissolved in 100 parts by mass of water, and 1.5 parts by mass of a polyamide epoxy additive (Taoka Chemical Co., Ltd., trade name "Sumirez Resin 650 (30)", a 30% by mass aqueous solution of solid content concentration) as a water-soluble epoxy resin was added to the aqueous solution to prepare an epoxy adhesive. The epoxy adhesive was applied to one surface of the polarizer obtained above.
[0177] A 60 μm-thick acrylic resin film (manufactured by Sumitomo Chemical Co., Ltd., trade name “Technolloy S001”) containing a UV absorber was bonded as a first protective layer onto the coating layer of the epoxy adhesive.
[0178] Then, in the same manner as above, an epoxy adhesive was applied to the other surface of the polarizer, and a zero phase difference film formed of an acrylic resin with a thickness of 40 μm was attached to the coating layer as a second protective layer. Then, the first protective layer and the second protective layer were bonded to the polarizer by drying at 80°C for 5 minutes. After bonding, the first protective layer and the second protective layer were aged at 40°C for 168 hours to obtain a polarizing plate with a total thickness of 130 μm, which was formed by laminating the first protective layer (layer thickness 60 μm), the polarizer (stretching ratio 5 times, layer thickness 23 μm) and the second protective layer (layer thickness 40 μm).
[0179] (3) Polarizer breaking stress test
[0180] A 50 mm wide and 150 mm long evaluation sample was cut from the obtained polarizing plate in such a manner that the major axis was aligned with the absorption axis of the polarizer. Using AUTOGRAPH (manufactured by Shimadzu Corporation, trade name "AGS-50NX"), one end of the evaluation sample in the length direction was grasped, and the other end was grasped in a 180-degree twisted state in an environment of a temperature of 23°C and a relative humidity of 60%. A 180° tensile test was performed at a tensile speed of 300 mm / min (according to JIS K7127:1999). The stress when the polarizing plate broke (breaking stress) was 3.1 N / 50 mm width.
[0181] (4) Thermal shrinkage test of polarizer
[0182] A 10 cm square evaluation sample is cut from the obtained polarizing plate in such a way that the absorption axis of the polarizer is parallel or perpendicular to each side of the evaluation sample. In an environment of a temperature of 23°C and a relative humidity of 60%, a metal ruler is used to measure the length of the side parallel to the absorption axis, and this is recorded as M1. After the evaluation sample is placed in an environment of 85°C for 144 hours, the length of the side with the largest thermal shrinkage is measured in an environment of a temperature of 23°C and a relative humidity of 60%, and this is recorded as M2. Based on the measured M1 and M2, the thermal shrinkage S (%) of the polarizing plate is calculated by the following formula (X). As a result, the thermal shrinkage S of the present polarizing plate is 1.9%.
[0183] S[%]={(M1-M2) / M1}×100…Formula (X)
[0184] (5) Reference Example: Preparation of Polarizing Plate A
[0185] Polarizer A was prepared in the same manner as in (1) to (2) above, except that a 60 μm thick triacetyl cellulose resin film (manufactured by Konica Minolta, Inc., trade name "KC4KR") was used instead of a 60 μm thick acrylic resin film as the first protective layer of the polarizer, and a 50 μm thick cyclic cycloolefin resin film (manufactured by ZEON Corporation, trade name "ZEONOR") was used instead of a 40 μm thick acrylic resin film as the second protective layer.
[0186] (6) Breaking stress test of polarizer A
[0187] The same evaluation method as in the above (3) was used to perform a breaking stress test on the polarizing plate A. As a result, the breaking stress of the polarizing plate A was 5.5 N / 50 mm width.
[0188] (7) Thermal shrinkage test of polarizer A
[0189] The same evaluation method as in the above (4) was used to derive the thermal shrinkage S of the polarizing plate A. As a result, the thermal shrinkage S of the polarizing plate A was 1.4%.
[0190] 2. Manufacturing of optical films with adhesive layers
[0191] (1) Preparation of adhesive composition
[0192] 100 parts by mass of the (meth)acrylate polymer (A-1) prepared in Preparation Example 1, 0.4 parts by mass of trimethylolpropane-modified toluene diisocyanate (manufactured by Soken Chemical & Engineering Co., Ltd., trade name "L-45") as a crosslinking agent (B), and 0.5 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent (C) were mixed, stirred thoroughly, and diluted with ethyl acetate to obtain a coating solution of an adhesive composition.
[0193] (2) Manufacturing of optical film with adhesive layer
[0194] The obtained coating solution of the adhesive composition was applied to the release-treated surface of a release sheet (SP-PET3811 manufactured by Lintec Corporation, thickness: 38 μm) having one surface of a polyethylene terephthalate film subjected to release treatment using a silicone release agent using a knife coater, and then heated at 90° C. for 1 minute to form a coating film of the adhesive composition.
[0195] Then, the polarizer and the coating film were laminated in such a manner that the surface of the second protective layer of the polarizer as an optical film obtained in the above 1. (1)-(2) was in contact with the exposed surface of the coating film, and aged at 23° C. and 50% RH for 7 days to obtain an optical film with an adhesive layer formed on the polarizer. In addition, the thickness of the formed adhesive layer was 20 μm.
[0196] [Examples 2 to 8, Comparative Examples 1 to 2]
[0197] An optical film with an adhesive layer was manufactured in the same manner as in Example 1, except that the type of (meth)acrylate polymer (A), the type and blending amount of the crosslinking agent (B), the blending amount of the silane coupling agent (C), and the blending amount of the antistatic agent (pyridinium salt-based ionic liquid (manufactured by KOEI CHEMICAL CO., LTD., trade name "IL-P18")) were changed as shown in Table 2.
[0198] Table 2 shows the respective proportions (solid content conversion value) of the adhesive composition when the (meth)acrylate polymer (A) is 100 parts by mass (solid content conversion value). The details of the abbreviations and the like described in Table 2 are as follows.
[0199] [Crosslinking agent (B)]
[0200] ·TDI: trimethylolpropane-modified toluene diisocyanate (manufactured by Soken Chemical & Engineering Co., Ltd., trade name "L-45")
[0201] Urate: Hexamethylene diisocyanate isocyanurate (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE HX")
[0202] [Test Example 1] (Measurement of Molecular Weight Distribution)
[0203] The molecular weight distribution of the (meth)acrylate polymer (A) prepared in Preparation Examples 1 to 5 was measured by gel permeation chromatography (GPC) under the following measurement conditions. Then, the weight average molecular weight (Mw), number average molecular weight (Mn), dispersion (Mw / Mn), peak molecular weight (Mp), and the amount of components with a molecular weight of 3 million or more were derived by standard polystyrene conversion. The results are shown in Table 1.
[0204] <Measurement Conditions>
[0205] ·GPC measuring apparatus: manufactured by TOSOH CORPORATION, HLC-8020
[0206] ·GPC column (passed in the following order): manufactured by TOSOH CORPORATION
[0207] TSK guard column HXL-H
[0208] TSK gel GMHXL (×2)
[0209] TSK gel G2000HXL
[0210] ·Test solvent: tetrahydrofuran
[0211] ·Measurement temperature: 40℃
[0212] [Test Example 2] (Viscosity measurement)
[0213] The (meth)acrylate polymer (A) prepared in Preparation Examples 1 to 5 is dissolved in the mixed solvent of ethyl acetate and acetone together with its polymerization solvent in such a manner that the concentration of the (meth)acrylate polymer (A) prepared in Preparation Examples 1 to 5 in the mixed solvent is 20% by mass. At this time, considering the polymerization solvent of the (meth)acrylate polymer (A), the respective amounts are adjusted in such a manner that the mass ratio of ethyl acetate to acetone is 85:15. Using a B-type viscometer, the viscosity (mPa·s) of the obtained solution is measured at 60 rpm using a No. 4 fixture. In addition, the measurement is carried out in an environment of a temperature of 23°C±5°C and a humidity of 50±5%. The results are shown in Table 1.
[0214] [Test Example 3] (Measurement of gel fraction)
[0215] The optical film with adhesive layer obtained in the examples and comparative examples was cut into a size of 80 mm × 80 mm, and its adhesive layer was wrapped in a polyester mesh (mesh size 200), and its mass was weighed using a precision balance, and the mass of the above-mentioned mesh alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was recorded as M1.
[0216] Then, at room temperature (23°C), the adhesive wrapped in the polyester net is immersed in ethyl acetate for 24 hours. Then, take out the adhesive, air-dry it for 24 hours at a temperature of 23°C and a relative humidity of 50%, and further dry it in an oven at 80°C for 12 hours. After drying, weigh its mass with a precision balance, subtract the mass of the net alone, and calculate the mass of the adhesive itself. The mass at this time is recorded as M2. The gel fraction (%) is expressed as (M2 / M1)×100. The results are shown in Table 2.
[0217] [Test Example 4] (Durability Evaluation)
[0218] The optical films with adhesive layers obtained in the examples and comparative examples were cut to prepare samples of 233 mm × 309 mm in size. The release sheet was peeled off from the sample, and the sample was attached to an alkali-free glass (Eagle XG manufactured by Corning Incorporated) via the exposed adhesive layer, and then pressurized at 0.5 MPa and 50° C. for 20 minutes using an autoclave manufactured by KURIHARA SEISAKUSHO Co., Ltd.
[0219] Then, the samples were placed in the following three durability conditions and after 250 hours, the presence or absence of floating or peeling was checked using a 10-fold magnifying glass. The evaluation criteria are as follows. The results are shown in Table 2.
[0220] ◎: No lifting or peeling was observed.
[0221] ○: Floating or peeling with a size of 0.5 mm or less was observed.
[0222] △: Floating or peeling with a size of more than 0.5 mm and 1.0 mm or less was observed.
[0223] ×: Floating or peeling with a size exceeding 1.0 mm was observed.
[0224] <Durability Conditions>
[0225] Heat resistance: 80℃ drying
[0226] ·Humidity: 60℃, relative humidity 90%RH
[0227] ·HS: Thermal shock test of 30 minutes each, 200 cycles
[0228] [Test Example 5] (Reoperability evaluation)
[0229] A sample of 25 mm in width and 100 mm in length was cut from the optical film with an adhesive layer obtained in the examples and comparative examples, and the peeling sheet was peeled off. After being attached to an alkali-free glass (manufactured by Corning Incorporated, product name "Eagle XG") via the exposed adhesive layer, it was pressurized at 0.5 MPa and 50° C. for 20 minutes using an autoclave manufactured by KURIHARA SEISAKUSHO Co., Ltd. Then, after being left at 50° C. and 50% RH for 2 days, the optical film with an adhesive layer was peeled off from the alkali-free glass using a tensile tester (manufactured by ORIENTEC CORPORATION, product name "TENSILON") at a peeling speed of 300 mm / min and a peeling angle of 180 degrees, and the adhesive force at this time was measured (adhesion after 2 days at 50° C.; N / 25 mm). The conditions not described here were measured in accordance with JIS Z0237:2009.
[0230] The re-operability of each sample was evaluated based on the following criteria based on the adhesive strength after 2 days of attachment at 50° C. and the presence or absence of breakage of the optical film when measuring the adhesive strength (when peeling off). The results are shown in the table.
[0231] ◎: Adhesion after 2 days at 50°C is less than 10.0N / 25mm, and there is no breakage of the optical film
[0232] ○: Adhesion after 2 days at 50°C is less than 10.0 N / 25 mm, and the optical film is broken.
[0233] ×: Adhesion strength after 2 days at 50°C is 10.0 N / 25 mm or more
[0234] [Test Example 6] (Evaluation of processability during coating)
[0235] In the manufacturing process of the optical film with an adhesive layer of the embodiment and the comparative example, when the coating solution of the adhesive composition is applied to the release-treated surface of the release sheet, it is visually confirmed whether vein-like unevenness is generated. In addition, after the coating solution of the adhesive composition is applied, it is visually confirmed whether bubbles are generated when it is dried, and the processability during coating is evaluated according to the following criteria.
[0236] ◎: No vein-like unevenness or bubbles were observed
[0237] ○: Slight vein-like irregularities or bubbles were observed
[0238] △: Slight vein-like irregularities and bubbles were observed
[0239] ×: Vein-like irregularities and bubbles were significantly observed.
[0240] [Table 1]
[0241]
[0242] [Table 2]
[0243]
[0244] As can be seen from Table 2, the optical films with adhesive layers obtained in Examples are excellent in durability and reworkability. In addition, the adhesive compositions containing the (meth)acrylate polymer (A) used in Examples have good processability during coating.
[0245] Industrial Applicability
[0246] The adhesive composition, adhesive, adhesive sheet, and optical film with an adhesive layer of the present invention are suitable for laminating a polarizing plate and a liquid crystal cell, for example, a film having an acrylic resin layer as a polarizer protective layer.
Claims
1. An adhesive agent, which is an adhesive agent obtained by cross-linking an adhesive composition containing a (meth)acrylate polymer (A) and a cross-linking agent (B), characterized in that: The weight average molecular weight (Mw) of the (meth)acrylate polymer (A) is 900,000 to 2,000,000. In the molecular weight distribution of the (meth)acrylate polymer (A) measured by gel permeation chromatography, the amount of components having a molecular weight of 3,000,000 or more is 15% by mass or less, and the peak molecular weight (Mp) is 800,000 or more and 1,200,000 or less, The viscosity of the (meth)acrylate polymer (A) when dissolved in a mixed solvent of ethyl acetate and acetone containing 85% by mass of ethyl acetate so as to have a concentration of 20% by mass is 5000 mPa·s or more and 10000 mPa·s or less, The (meth)acrylate polymer (A) contains a monomer having a hydroxyl group in the molecule as a monomer unit constituting the polymer. The crosslinking agent (B) reacts with the hydroxyl group of the (meth)acrylate polymer (A). The adhesive has a gel fraction of 50% to 80%.
2. The adhesive according to claim 1, characterized in that The (meth)acrylate polymer (A) is polymerized without using a solvent having a boiling point of 70° C. or less. 3 . An adhesive sheet comprising an adhesive layer formed of the adhesive according to claim 1 .
4. An optical film with an adhesive layer, comprising: An optical film having at least one acrylic resin layer; and The adhesive layer formed of the adhesive according to claim 1 is laminated on at least one surface of the optical film.
5. The optical film with an adhesive layer according to claim 4, characterized in that: The optical film is a polarizing plate having the acrylic resin layer as a polarizer protective layer.
Citation Information
Patent Citations
Adhesive and adhesive sheet
JP2017193608A
Adhesive and adhesive sheet
CN102888200A
Pressure-sensitive adhesive sheet
JP2005126702A
Crosslinkable resin composition, adhesive for optical member, and optical member
JP2009173875A